#### Answer

$$ h_z(3,0) =3 .$$

#### Work Step by Step

Since $ h(x,z))=e^{xz-x^2z^3}$, then by the chain rule, we have
$$ h_z=e^{xz-x^2z^3}(x-3x^2z^2)=(x-3x^2z^2)e^{xz-x^2z^3}.$$
Hence, we get
$$ h_z(3,0)=(3-0)e^{0}=3 .$$

Chegg costs money, GradeSaver solutions are free!

Published by
W. H. Freeman

ISBN 10:
1464125260

ISBN 13:
978-1-46412-526-3

$$ h_z(3,0) =3 .$$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.